Development of a control system with PC interface for a selective compliant articulated robot arm - Buyao, Reynald C.; Nirza, May C. (2010)
SCARAs have been used for various industrial applications such as pick and place, palletizing, and assembling, for more than 40 years. Although more flexible articulated robot arms have taken over some of their jobs, there is still a great need for SCARAs. They offer higher speed, heavier payload, capacity and require smaller workspace. This project aimed to assemble a low cost control system that will be used to drive the four motors of the Adept Cobra 600 and must be able to move it around its specified workspace. The project is divided into: design and construction of the motor drivers, feedback detection and motor control using the microcontroller board, development of a simple PC interface, and integration and testing of the whole system.
Thesis (B.S. Electronics and Communications Engineering & B.S. Computer Engineering ) -- University of the Philippines, Diliman
Keywords: Robots, Industrial; Robots -- Control systems -- Design and construction; Selective compliant articulated robot arm; Adept Cobra 600.